Recovery and reuse of alginate in an immobilised algae reactor - Murujew, Olga; Whitton, Rachel; Kube, Matthew; Fan, Linhua; Roddick, Felicity; Jefferson, Bruce; Pidou, Marc (Taylor and Francis, 2019)
The use of microalgae for nutrients removal from wastewater has attracted more attention in recent years. More specifically, immobilized systems where algae cells are entrapped in beads in a matrix of a polysaccharide such as alginate have shown a great potential for nutrients removal from wastewater to low levels with reduced retention times and hence smaller footprint. However, a significant operational cost in the up-scaling of alginate-immobilized algae reactors will be the gelling agent alginate. To reduce expenditure of this consumable a proof-of-concept is given for an alginate recycling method using sodium citrate as a dissolving agent. Using algae beads made from virgin and recycled alginate yielded comparable removal rates for both phosphorus and nitrogen compounds from wastewater. At labscale, an alginate recovery of approximately 70% can be achieved which would result in a net operational cost reduction of about 60%.
Keywords: Alginate; immobilized algae,; phosphorus removal; recovery; recycle